2013
DOI: 10.1212/wnl.0b013e31828ab26f
|View full text |Cite
|
Sign up to set email alerts
|

Increased childhood incidence of narcolepsy in western Sweden after H1N1 influenza vaccination

Abstract: Pandemrix vaccination is a precipitating factor for narcolepsy, especially in combination with HLA-DQB1*0602. The incidence of narcolepsy was 25 times higher after the vaccination compared with the time period before. The children in the postvaccination group had a lower age at onset and a more sudden onset than that generally seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 21 publications
7
112
1
8
Order By: Relevance
“…Moreover, autoantibodies recognizing different antigenic targets expressed in the central nervous system (CNS) have been identified in the serum and cerebrospinal fluid (CSF) of narcoleptic patients (9-11). Finally, a dramatic increase in the incidence of T1N has been observed in Northern Europe during the 2009-2010 vaccination campaigns against pandemic H1N1 influenza virus using the Pandemrix vaccine (12)(13)(14). The immune mechanisms involved remain unknown, although molecular mimicry is strongly suspected (9,15).…”
Section: Cd8 T Cell-mediated Killing Of Orexinergic Neurons Induces Amentioning
confidence: 99%
“…Moreover, autoantibodies recognizing different antigenic targets expressed in the central nervous system (CNS) have been identified in the serum and cerebrospinal fluid (CSF) of narcoleptic patients (9-11). Finally, a dramatic increase in the incidence of T1N has been observed in Northern Europe during the 2009-2010 vaccination campaigns against pandemic H1N1 influenza virus using the Pandemrix vaccine (12)(13)(14). The immune mechanisms involved remain unknown, although molecular mimicry is strongly suspected (9,15).…”
Section: Cd8 T Cell-mediated Killing Of Orexinergic Neurons Induces Amentioning
confidence: 99%
“…About 67 % of the Swedish children were vaccinated against | 33 pH1N1 with Pandemrix [214]. A study in western Sweden found a 25-fold higher risk of developing narcolepsy after Pandemrix vaccination, and all narcolepsy patients in this study had HLA DQB1*0602 [223]. The report from the Swedish Medical Products Agency (MPA) reported a 6.6 higher risk in children <19 years of age for developing narcolepsy with cataplexy after vaccination [214].…”
Section: Narcolepsymentioning
confidence: 76%
“…Excipients: 1) A few months after Pandemrix ® (the influenza A vaccine containing the AS03 adjuvant) administration following the influenza A (H1N1) epidemic in Europe, more than 800 children across Europe (especially in Sweden and Finland) have been diagnosed with narcolepsy-cataplexy [21]. At present, assessments of the causal mechanisms about the adjuvant remains to be investigated and long term epidemiological studies about AS03-adjuvanted influenza A (H1N1) pandemic vaccine prepared with the European inactivation/ purification protocol are recommended [22].…”
Section: Adverse Events Following Immunization (Aefi)mentioning
confidence: 99%